2018
DOI: 10.1080/02673843.2018.1509793
|View full text |Cite
|
Sign up to set email alerts
|

Online communication, peer relationships and school victimisation: a one-year longitudinal study during middle adolescence

Abstract: This study aimed to analyse how different styles of online and offline communication were associated in middle adolescence with certain indicators of the quality of peer relationships and school victimisation. A longitudinal study with two waves separated by one year was conducted, in which 882 adolescents aged 13-16 years old from Andalusia (Spain) completed self-report measures. Results showed that online communication was very frequently used to talk with friends, even more often that offline means. Cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…This includes increased initiation of relationships, better friendship quality, greater perceived social support and feelings of belonging (Antheunis, Schouten, & Krahmer, 2016;Desjarlais, Gilmour, Sinclair, Howell, & West, 2015;Shapiro & Margolin, 2014;Valkenburg & Peter, 2007b). Moreover, the benefits of online disclosure extend to offline relationships, with longitudinal data showing that it increases the initiation of offline friendships (Gomez-Baya, Rubio-Gonzalez, & Matos, 2018). The greater ease and controllability of communicating personal or potentially embarrassing information online is thought to underlie the relationship between online disclosure and social connectedness (Shapiro & Margolin, 2014;Valkenburg & Peter, 2009a).…”
Section: Behavioral Trends Of Adolescent Self-disclosurementioning
confidence: 99%
“…This includes increased initiation of relationships, better friendship quality, greater perceived social support and feelings of belonging (Antheunis, Schouten, & Krahmer, 2016;Desjarlais, Gilmour, Sinclair, Howell, & West, 2015;Shapiro & Margolin, 2014;Valkenburg & Peter, 2007b). Moreover, the benefits of online disclosure extend to offline relationships, with longitudinal data showing that it increases the initiation of offline friendships (Gomez-Baya, Rubio-Gonzalez, & Matos, 2018). The greater ease and controllability of communicating personal or potentially embarrassing information online is thought to underlie the relationship between online disclosure and social connectedness (Shapiro & Margolin, 2014;Valkenburg & Peter, 2009a).…”
Section: Behavioral Trends Of Adolescent Self-disclosurementioning
confidence: 99%
“…Studies that examined the rich-get-richer and poor-get-richer hypotheses with regard to friendship closeness have yielded inconsistent results 3 , 5 , 7 , 8 . Some studies found that mainly socially rich adolescents benefit from social media use 3 , others that mainly socially poor adolescents benefit from social media use 8 , and yet others supported both hypotheses 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examined the rich-get-richer and poor-get-richer hypotheses with regard to friendship closeness have yielded inconsistent results 2,[4][5][6] . Some studies found that mainly rich adolescents benefit from social media use 6 , others that mainly poor adolescents benefit from social media use 5 , and yet others supported both hypotheses 4 .…”
mentioning
confidence: 99%
“…Studies that examined the rich-get-richer and poor-get-richer hypotheses with regard to friendship closeness have yielded inconsistent results 2,[4][5][6] . Some studies found that mainly rich adolescents benefit from social media use 6 , others that mainly poor adolescents benefit from social media use 5 , and yet others supported both hypotheses 4 . An important explanation for this inconsistency in the literature may be that previous studies have overlooked three theoretical principles of human development [7][8][9] and media effects 10,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation